Pengaruh generator HHO dan etanol terhadap performa dan emisi gas buang mesin bensin - Setiawan, N.D.C.; Prasetiyo, D.H.T.; Wahyudi, D. (Universitas Mataram, 2022)
The large number of motorized vehicles in Indonesia cannot be separated from the rapid population growth. Fuel is one of the important components in vehicles, this is because the fuel produces heat energy to be converted into mechanical energy. So far, ordinary people only use fuel oil (BBM) based on the price per liter, assuming all fuel can be used in their vehicles. In fact, to get maximum performance and low exhaust emissions, it requires high octane fuel. The purpose of this study was to determine the effect of adding ethanol and HHO to fuel on engine performance and the resulting exhaust emissions. The test sample consisted of Pertamax fuel which was then mixed with 10% ethanol with the addition of HHO. Furthermore, the process of testing the performance of the vehicle's engine and the resulting exhaust emissions. The test results show that there is an increase in power and torque of 7.77 hp and 7.54 N.m, respectively, in the test of fuel mixing with the addition of HHO. Then the results of the exhaust gas test resulted in a decrease in CO and HC while the CO2 level increased by testing the mixing of fuel with ethanol accompanied by the addition of HHO. The average percentage scores for each test were 15.02%, 17.79%, and 16.72%.